The Chemopreventive Potential of Diosmin and Hesperidin for COVID-19 and Its Comorbid Diseases - Utomo, Rohmad Yudi; Ikawati, Muthi'; Putri, Dyaningtyas Dewi Pamungkas; Salsabila, Irfani Aura; Meiyanto, Edy (Indonesian Society for Cancer Chemoprevention, 2020)
The COVID-19 becomes worse with the existence of comorbid diseases such as cardiovascular diseases, metabolic syndromes, inflammation, degenerative diseases, as well as cancer. Therefore, a comprehension approach is needed to combat such comorbid conditions, not only focusing on the virus infection and replication but also directed to prevent the raising comorbid symptoms. This study analyzed the potential natural compounds, especially diosmin and hesperidin, as an anti-SARS-CoV-2 and chemopreventive agent against several COVID-19 comorbid diseases by using an in-silico method. Diosmin and hesperidin together with other natural compounds and existing viral drugs (lopinavir, nafamostat, and comastat) were docked into several proteins involved in SARS-CoV-2 infection and replication namely SARS-CoV-2 protease (PDB:6LU7), spike glycoprotein-RBD (PDB:6LXT), TMPRSS2, and PD-ACE2 (PDB:6VW1) using MOE software. The interaction properties were determined under docking score values. The result exhibited that diosmin and hesperidin performed superior interaction with all the four proteins compared to the other compounds, including the existing drugs. Moreover, under literature study, diosmin and hesperidin also elicit good chemopreventive properties against cardiovascular disorder, lung and kidney degeneration, as well as cancer development. In conclusion, diosmin and hesperidin possess high opportunity to be used for the COVID-19 and its the comorbid diseases as chemopreventive agents.Keywords: chemoprevention, COVID-19, diosmin, hesperidin, SARS-CoV-2 infection